W.H. Auden encyclopedia - Izzo, David Garrett (Mcfarland, 2011)
"Born in 1907 and first published in the 1920s, W.H. Auden was hailed as the new T.S. Eliot and as the "coming" man, greatly influencing the future generations of angry young men with his thoughts on science, religion, and the relationship between the two." "This book is an exhaustive reference to Auden's life and work. Those new to Auden will find the work a comprehensive introduction, while Auden scholars will appreciate the quick access it offers to the details of all his poems, plays, libretti, and other pieces of writing." "Also included are entries on the people who were closest and most important to Auden, such as fellow writers Christopher Isherwood and Cecil Day Lewis, and on significant events in his life, such as his arrival in America, his decision to embrace Christianity, and his search in science and religion for answers to the deep questions of life and existence."--P [4] of cover